Yak milk and its health benefits: a comprehensive review - Kalwar, Qudratullah; Ma, Xiaoming; Xi, Bin; Korejo, Rashid Ali; Bhuptani, Deepesh Kumar; Chu, Min; Yan, Ping (Frontiers in Veterinary Science, 2023)
Abstract: Yak milk has various potential health benefits due to its high nutritional content and unique composition. It is an excellent source of protein, essential fatty acids, vitamins, and minerals, which can promote overall health and wellbeing. Yak milk may have potential therapeutic benefits for hypertension, as it contains peptides that have been shown to have antihypertensive effects. Yak milk has also been shown to possess antioxidant properties, which can help protect against oxidative stress and related health problems. Moreover, its fat contains higher levels of beneficial fatty acids, such as conjugated linoleic acid (CLA) and omega-3 fatty acids, which have been linked to various health benefits, including reducing inflammation, improving heart health, and supporting brain function. Moreover, further research is needed to fully understand the potential health benefits of yak milk, its unique composition and high nutritional content suggest that it may offer numerous health benefits and could be a valuable addition to a healthy diet.